Succeeding at the Top: A Self-Paced Workbook for Newly Appointed CEOs and Executives - Liebowitz, Bernard (Business Expert Press, 2010)
Ebook from IG Library ; This workbook is designed for CEOs, Executives and Senior Managers who have been assigned to a new position with sufficient authority, if not a mandate, to enact change in the organization. Even in situations where there is no overt instruction to effect change, the New Executive is expected to improve the situation, which in fact means to change things. It is expected of him or her, wittingly or unwittingly. However, the high failure rate of New Executives can be explained either by a too-rapid rush to change, or, its opposite–waiting until it’s too late.